ASSESSMENT OF NITROGEN RETENTION FROM MAIZE CROP AND WETLAND DITCH PLANTS RESIDUES BY VERMICOMPOSTING - S. T. Raza; Z. Bo1; T. J. Liang; Z. Ali3; H. Iqbal; R. Ahmad (Journal of Animal and Plant Sciences, 2020)
An option for ecological engineers is to increase the yield of the agroecosystem with the reuse of nitrogen through the application of vermicomposting with Eisenia fetida prepared by using crop residues and wetlands plants jointly. The experiment was designed considering recycling and reuse of the agricultural crop (Zea mays) residues and native wetland plants (Canna indica, Cyperus alternifolius, Acorus calamus and Hydrocotyle vulgaris) and pig manure found in Sichuan Basin, China. A total of fourteen treatments (V1-V14) were prepared and the experiment for V1 to V4 treatments was set-up in cemented plots and separate experiments were set-up for V5-V8 and V9-V14 in containers for three months (September to December 1517). The amount of total nitrogen (TN) improved in all the treatments (V1-V14) throughout experimental period of 90 days. In case of group 1, considering major parameters like TOC, C:N ratio and TN, combination of Zea mays and Canna indica (V3) can be regarded as most suitable combination for vermicomposting. In the second group, V6 treatment [(Cyperus alternifolius (60%): Pig manure (40%)) was found to be suitable based on TN recovery. The mixture of combined Zea mays (50%), Cyperus alternifolius (5%), Acorus calamus (5%) and pig manure (V13) increased 76% TN and can be regarded as best in group 3 based on percent change. Results indicated that ditch plants and crop residues can be used as substrates in vermicomposting for nutrient recovery.
Keywords: Crop residues; Wetland plants; Vermicompost; Nitrogen; Sichuan Basin